A framework to estimate return on investment (ROI) from funding of research, development, commercialization and innovation (RDCI) in Malaysia: methods and protocol / Ahmad Taufek Abdul Rahman, Shaliza Ibrahim and Shukor Abd Razak - Abdul Rahman, Ahmad Taufek; Ibrahim, Shaliza; Abd Razak, Shukor (UiTM Press, 2021)
Every year, the Government had allocated and invested a lot of money in the Higher of Education Institute (HEI) sector, aiming to empower the research activities in the HIE sector. Research grant funding is crucial in achieving higher revenue growth through higher quality education at all levels. Return on Investment (ROI) is often used to measure total return on investment compared to investment costs. However, it is difficult to calculate ROI from Kementerian Pengajian Tinggi (KPT) grants which mainly are fundamental based grants as the main outputs are publications and talents (intangibles). There are limited literature appears to have proposed a generic ROI measurement and calculation from Research, Development, Commercialization and Innovation (RDCI) investments. This project aims to identify whether the research grant at the Ministry of Higher Education (MOHE) provides a suitable ROI based on funding provided. Although this is the first country-wide attempt to formulate the ROI of research funding scheme in Malaysia, it remains to be seen that ROI is a suitable measurement of success. There are many models to measure the efficiency of the annual research funds allocation. The analysis is context-specific and assesses the definition and calculation of the model and the benefits. Hence the outcome from this ROI analysis tends to be relative and restricted to this specific environment.